Creative Production Strategies for Algorithmic Da'wah: A Case Study of the Islamic Short Film Waaqimussolah - Eca Mariska; Khomsahrial Romli; Nadya Amalia Nasution (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
Islamic da'wah film scholarship has focused predominantly on textual analysis of completed works, leaving creative production processes that determine digital reach unexamined. This study examines creative strategies in producing Waaqimussolah (2024) by Fiqri Fox as a digitally distributed Islamic short film. Qualitative descriptive approach; data from in-depth interviews with five key informants, platform analytics, and production documentation; analyzed through Rhodes 4P framework extended with a Platform dimension. Four creative-algorithmic intersections identified: (1) 94.8% FYP-driven TikTok discovery; (2) duration compressed from 10–11 minutes to 8:14 due to platform constraints; (3) two-stage funnel yielding 858,519 TikTok views and 39,200 YouTube views (84% search traffic); (4) WhatsApp community sharing (49.4% external traffic) as unplanned third distribution layer. Rather than merely reflecting distribution performance, these metrics demonstrate that platform logic actively shapes creative production decisions at the levels of narrative pacing, hook design, and distribution sequencing, supporting Platform as a distinct and empirically observable dimension within the creativity framework. Algorithmic da'wah describes a productive intersection, not a replacement, of spiritual intentionality and platform logic: creative authority remains with the filmmakers even as specific decisions are negotiated against algorithmic constraints. This study proposes a 5P framework extension, Person, Process, Press, Product, and Platform, and offers an empirically grounded production model for low-budget Islamic digital filmmakers seeking to reach younger, platform-native audiences without compromising da'wah intent.